2020
DOI: 10.3389/fonc.2019.01575
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel LncRNA, AC091729.7 Promotes Sinonasal Squamous Cell Carcinomas Proliferation and Invasion Through Binding SRSF2

Abstract: Long non-coding RNAs (lncRNAs) play important roles in various biological progresses of carcinogenesis. However, the function of lncRNAs in human sinonasal squamous cell carcinoma (SNSCC) remains greatly unclear. In the current study, lncRNA AC091729.7 expression was examined in SNSCC samples by using microarray, RNA in situ hybridization (ISH) and real-time fluorescence quantitative PCR (qRT-PCR). Cell viability, colony-formation, wound-healing, and transwell assays were applied to SNSCC cells. Xenograft mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…A careful literature search revealed that AC023310.4 which located on chromosome 15q11.2 was first reported here, and its biological function has not been reported to date. AC091729.1 is located on chromosome 7, Yu et al identified another version AC091729,7 plays a carcinogenic role and serves as a novel biomarker and latent curative target in sinonasal squamous cell carcinoma patients ( Yu et al, 2019 ). LINC01564 is located on chromosome 6p12.1, Zhang et al reported that LINC01564 was associated with hepatocellular carcinoma cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…A careful literature search revealed that AC023310.4 which located on chromosome 15q11.2 was first reported here, and its biological function has not been reported to date. AC091729.1 is located on chromosome 7, Yu et al identified another version AC091729,7 plays a carcinogenic role and serves as a novel biomarker and latent curative target in sinonasal squamous cell carcinoma patients ( Yu et al, 2019 ). LINC01564 is located on chromosome 6p12.1, Zhang et al reported that LINC01564 was associated with hepatocellular carcinoma cell survival.…”
Section: Discussionmentioning
confidence: 99%
“… 73 Using RNA immunoprecipitation (RIP), lncRNA AC091729.7 has been found to directly combine with the serine/arginine-rich splicing factor 2 and promote HNSCC cell proliferation, migration and invasion, and tumor growth in vivo. 74 LncRNA MIR31HG targets HIF-1α and p21, promoting cell-cycle progression and inhibiting cell apoptosis, thus facilitating HNSCC cell proliferation and tumorigenesis. 75 Moreover, lncRNA DANCR is responsible for NPC metastasis and the hypoxia phenotype.…”
Section: Mechanism Of Lncrnas In Hnsccmentioning
confidence: 99%
“…In another study, we investigated the role of SRSF2 in T cell exhaustion during tumorigenesis and demonstrated that SRSF2 expression is significantly elevated in exhausted T cells, and that SRSF2 knockdown reverses the exhaustion of T cells by epigenetically regulating the expression of multiple immune checkpoint molecules [6]. In addition, an increasing number of studies have recently shown that SRSF2 gene mutation and dysregulated SRSF2 expression are significantly associated with acute myeloid leukemia (AML) [16,17], myelodysplastic syndromes [18][19][20], systemic mastocytosis [21,22], chronic myelomonocytic leukemia [23][24][25], lung carcinoma [26,27], hepatocellular carcinoma [28], and sinonasal squamous cell carcinoma [29]. These findings indicate that SRSF2 functions as a promising therapeutic target for various diseases.…”
Section: Introductionmentioning
confidence: 99%